Contractual nature of comfort letters. Semiotics, pragmatics and Private International Law - Mengual Pujante, Gabriel (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This paper analyses the contractual nature of comfort letters under Private International Law of the European Union, a legal qualification that derives from the existence of a commitment or obligation in each of its modalities. In order to go deeper, this paper offers a semiotic and pragmatic approach on the legal business mentioned above. To this aim, the paper analyses comfort letters as language acts or acts of communication, a methodology from which notable practical consequences can be extracted.
Keywords: Comfort letters; semiotics; pragmatics; contractual nature; commitment; Private International Law